Utilization of Potato Flour in Making Pukis Cake - dikki zulfikar; Wiwik Gusnita (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2019)
This research is motivated by the use of potato flour in food processing is still small. Potato flour has a high enough nutritional value for protein. This study aims to analyze the effect of 50% potato flour substitution on the quality of paint in terms of volume, shape, color, aroma, texture and taste. This type of research is an experiment with three repetitions. To get the results of the study organoleptic tests were carried out by 15 panelists, namely students of the D3 and S1 at culinary department. Organoleptic test results with 3 repetitions showed that the quality of the use of potato starch in the manufacture of paint was volume swell, same and semicircular shape, yellow color, aroma of vanilla and potato starch, porous texture, sweet taste and taste of potato starch.